1997
DOI: 10.1152/ajpcell.1997.273.6.c1801
|View full text |Cite
|
Sign up to set email alerts
|

Reappearance of the minor α-sarcomeric actins in postnatal muscle

Abstract: The postnatal expression profiles of α-sarcomeric actin transcripts and protein are quantified in mouse striated muscles from birth to postnatal day 56 by Northern and Western blot analyses. α-Cardiac actin (α-CA) transcripts transiently increase between 12 and 21 days after birth in the quadriceps muscle, reaching ∼90% that found in the adult mouse heart. Although α-CA is the α-sarcomeric actin isoform expressed in the immature fiber, the expression profiles of other contractile protein isoforms indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…We did, however, detect low-level X-gal staining in the heart, and, though this finding was somewhat surprising because of the lack of detection of the MCM protein in the heart, it is consistent with the findings of Collins et al [26]. Using a quantitative Northern blot method, Collins and colleagues found a low level of α-skeletal actin mRNA in the adult mouse heart [26]. Thus, the minor amount of X-gal staining in the heart likely reflects the function of the HSA promoter rather than a transgenic artifact or leakiness of the MCM system.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We did, however, detect low-level X-gal staining in the heart, and, though this finding was somewhat surprising because of the lack of detection of the MCM protein in the heart, it is consistent with the findings of Collins et al [26]. Using a quantitative Northern blot method, Collins and colleagues found a low level of α-skeletal actin mRNA in the adult mouse heart [26]. Thus, the minor amount of X-gal staining in the heart likely reflects the function of the HSA promoter rather than a transgenic artifact or leakiness of the MCM system.…”
Section: Resultssupporting
confidence: 92%
“…Importantly, no X-gal staining was observed in vehicle-treated samples, confirming that the MCM-mediated recombination requires tamoxifen treatment. We did, however, detect low-level X-gal staining in the heart, and, though this finding was somewhat surprising because of the lack of detection of the MCM protein in the heart, it is consistent with the findings of Collins et al [26]. Using a quantitative Northern blot method, Collins and colleagues found a low level of α-skeletal actin mRNA in the adult mouse heart [26].…”
Section: Resultssupporting
confidence: 89%
“…For example, expression levels of both skeletal actin and vascular smooth-muscle actin are increased, the former transiently, following work overload-induced hypertrophy in the adult rodent heart (2, 9, 27). Likewise, in the adult BALB/c mouse heart, there is a reduced level of cardiac actin associated with a 9.5-kb duplication of a part of the cardiac actin gene that results in the increased expression of skeletal actin (3,15). Furthermore, we have reported that cardiac-actin-null mice show increases in skeletal and vascular actin in their hearts (10).…”
Section: Discussionmentioning
confidence: 82%
“…27,28 Because ACTC expression might compensate for, or otherwise modulate, the effects of ␣-skeletal actin abnormalities, we assessed expression of these proteins in muscles from eight patients with, and three without, ACTA1 mutations ( …”
Section: Immunolocalization and Isoform Composition Of Sarcomeric Actinsmentioning
confidence: 99%